Babymouse : dragonslayer - Holm, Jennifer L.; Holm, Matthew (New York : Random House Children's Books, 2009)
An imaginative mouse who likes to read heroic fantasy novels finds herself on the school math team as it prepares to compete for the coveted Golden Slide Rule.
Keywords: Animals -- Fiction; Contests -- Fiction; Graphic novels; Humorous stories; Imagination -- Fiction; Mathematics -- Fiction; Mice -- Fiction; Schools -- Fiction; Graphic novels